Afterword: The Object Lessons of the Virtual Museum - Lynch, Deidre (Romanticism on the Net, 2023)
Emphasizing the mutability and volatility of Romantic matter, the essays collected in this special issue evoke a museum in motion. This afterword, however, focuses on a secondary line of argument running through Materialising Romanticism—this issue’s account of how the Romantics often used things to move themselves. To bring that account to the fore and demonstrate its continued relevance to our twenty-first-century pandemic moment, as to twenty-first-century distance learning, I explore the Romantic-era invention of concepts of armchair travel and armchair travelers—figures who use material objects to jump-start experiences of imaginative transport and of traveling in place. As an initial illustration of such uses, I engage with an early-nineteenth-century parlor amusement called the myriorama, which promised that an almost infinite number of landscapes could be created through the manipulation of only twelve or sixteen cards. I turn next to two Romantic-period literary examples—Xavier de Maistre’s memoir of house arrest and how-to book for mental travel, Voyage autour de ma Chambre, and the episode in Mansfield Park that dramatizes the lessons in both dwelling and escape that Austen’s heroine Fanny Price reads off the collectibles she has gathered up in the manor house’s old schoolroom.